Development of Coconut Oil Fermentation MethodS (Cocos Nucifera) Using Rhizopus SP Microbe - Wulandari, Retno; Hernowo Widodo (Green Publisher, 2022)
Generally, the manufacture of coconut oil still uses high temperatures so it requires a lot of energy or fuel. In this study, the manufacture of coconut oil was developed using the help of Rhizopus sp microbes with the fermentation method. The aim is to save fuel, little residue, low rancidity level, fragrant aroma, free of cholesterol-inducing compounds and to study the effect of microbial weight, fermentation time. The results obtained from the organoleptic test of coconut oil produced a savory taste, fragrant aroma and clear color, in accordance with SNI 7381:2008. The results of the chemical analysis test were pH 4, the free fatty acid value was 0.15%, the peroxide number was 2.97 mekO2/Kg and the saponification number was 246 MgKOH/gr in accordance with SNI 01-2902-1992. Then the microbial test was found Kapang of 1 and Khamar of < 1, in accordance with the standard SNI ISO 2157-1 (BPOM).